The complete mitochondrial genome and phylogenetic analysis of Syncrossus berdmorei (Blyth, 1860) (Cypriniformes: Botiidae) - Xing Peng Han; Lin Song; Quan Wang; Xiao Jiang Chen (Mitochondrial DNA. Part B. Resources)
The mitochondrial genome of Syncrossus berdmorei has yet to be characterized. In this study, we sequenced and analyzed its complete mitochondrial genome, which is 16,553 base pairs and comprises 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and two non-coding regions, showing a strong A + T bias. Phylogenetic analyses using maximum likelihood and Bayesian inference indicated a close evolutionary relationship between S. berdmorei and S. beauforti, suggesting that Leptobotia hengyangensis may warrant reclassification into the Sinibotia genus. This research provides a genetic resource for Syncrossus and enhances our understanding of the evolutionary history and taxonomic relationships within Botiidae.